The development and progress of health literacy in China - Li, Yuanyuan; Lv, Xiaofeng; Liang, Jun; Dong, Hengjin; Chen, Changgui (Frontiers in Public Health, 2022)
Limited health literacy is a serious public health problem. It is strongly associated with increased hospital admissions and readmission, poorer self-management, and health outcomes. It diminished management of chronic disease, lower health care quality, increased mortality, and higher healthcare expenditures. Understanding China’s current situation and the progress of health literacy levels are critical to achieving practical solutions for improving population health. This paper intended to provide a concise overview of the key milestones and specific practices in health literacy in China. We summarized the characteristics and changing profile of health literacy from 2008 to 2020 in China. We developed an intervention framework based on social ecosystem theory for improving health literacy in China. Meanwhile, some multi-level actionable recommendations were proposed. The study revealed that China has made obvious progress in improving health literacy in the last decades. Health literacy levels increased from 6.48% of the population in 2008 to 23.15% in 2020. Geographic disparities were substantial. The East performed better health literacy than the Central and West, and cities had higher adequate health literacy than rural areas. Social development index, age, and education level were highly associated with health literacy. A global joint effort to improve health literacy will be required. And we advocate a whole-of-society approach that involves the participation of the entire ecosystem around the targeted population.